KOMUNIKASI TERAPEUTIK PADA PENDAMPING PASIEN TUBERKULOSIS RESISTEN OBAT DI SURABAYA (Studi Kasus pada Yayasan Tuberkulosis di Surabaya) - Nada, Mauldey Salsania; Ade Firmannandya (Universitas Negeri Surabaya, 2025)
This study aims to analyze the implementation of therapeutic communication in caregiver of multi drug resistant tuberculosis patients in Surabaya involving caregiver of MDR patients at the Yayasan Rekat Peduli Indonesia, Yayasan Bhanu Yasa Sejahtera Surabaya, and Gerakan Eliminasi Tuberkulosis Surabaya. The analysis focuses on the therapeutic communication model, namely the informed model by Charles. This study uses a qualitative approach with a case study method. The results of the study show that there are 4 stages of therapeutic communication, namely pre-interaction, orientation, work, and termination. In supporting the process, there are several elements of therapeutic communication involved, namely sender, recipient, message, noise, feedback, and effect. The patient caregiver as the sender and the MDR patient as the recipient carry out two-way communication involving messages, both verbally and nonverbally. Based on the two-way communication shown and the effects on patients in the form of treatment decision making, there is an therapeutic communication model, namely the informed model.